Admixture of ancient mitochondrial lineages in three‐spined stickleback populations from the North Pacific. (28th November 2014) - Lescak, Emily A.; Marcotte, Robert W.; Kenney, Leah A.; von Hippel, Frank A.; Cresko, William A.; Sherbick, Mary L.; Colgren, Jeffrey J.; Andrés López, J.; Riddle, Brett
Abstract Aim We test the hypothesis that the North Pacific coastline from British Columbia to the Kuril Islands forms a broad region of admixture between two divergent mitochondrial‐genome (mtDNA) lineages in three‐spined stickleback (Gasterosteus aculeatus): the Euro‐North American (ENA) and Trans‐North‐Pacific (TNP or Japanese) clades. We test whether distance is the primary determinant of geographical patterns of haplotype distributions and whether deep‐water trenches in the Aleutian and Kuril archipelagos impede gene flow. Location Coastal marine and freshwater sites from the Kuril Islands (north‐western Pacific Ocean) to Oregon (north‐eastern Pacific Ocean). Methods We determined the mtDNA clade for 1327 individuals from 67 locations across 8000 km of the North Pacific using restriction fragment length polymorphism assays of the cytochrome b mitochondrial gene. We supplemented this with published clade designations from coastal Pacific populations and applied generalized linear modelling and Mantel tests. We used analysis of molecular variation (AMOVA) to test for significant partitioning of genetic variation by deep‐water trenches. Results The western boundary of the ENA clade was Simushir (Kuril Islands) and the eastern boundary of the TNP clade was British Columbia. Coastline distance from Japan was a significant predictor of TNP abundance. Clade composition variance was high at small geographical scales, in apparent discordance with the broader‐scale pattern of admixture. Deep‐water trenches were not found to significantly partition genetic variation in the Aleutian and Kuril island chains. Main conclusions The North Pacific coastline forms a broad region of secondary contact between divergent mitochondrial lineages, but with clear western and eastern boundaries. Patterns of clade abundance in the Kuril and Aleutian islands are similar to those observed in other taxa, suggesting shared biogeographical histories and common barriers shaping species distributions along the North Pacific coast. Overall patterns of clade distributions are likely to be driven by a combination of factors, including geomorphological impediments to migration, ecology, asymmetrical dispersal patterns and differences in timing of population expansions.